THE EXPLORATION TO THE PATAGONIA OF FATHER NICOLÁS MASCARDI: AN EXPERIENCE ABOUT THE POSSIBILITIES AND THE LIMITS OF KNOWLEDGE IN THE XVII CENTURY - Acuña Fariña, Constanza (Revista de Historia Social y de las Mentalidades, 2015)
In 1670 the Jesuit Nicolás Mascardi (Sarzana,  1624 – Río Deseado, 1674) directed the mission  of Nahuel Huapi refoundation. Following his  predecesor Diego de Rosales, Mascardi wanted  establish an indigene reduction for puelches,  poyas y tehuelches, for to be the starting point of  “flying” missions until the Magallanes channel.  From the find of the Mascardi letters to his  master Athanasius Kircher, sent from the south of  Chile –in this moment at the Archivo Histórico  de la Compañía in Rome- this article pretend to  analyze how converge the baroque imagination,  the mentality and the scientific practises of the  x VII century in the italian jesuit project; to try  understand why his plan was precipitated down  the historical events, which marked his missioner  project destination and his early death at the hands  of tehuelches, nearby Deseado river in Patagonia  Argentina. The relationship of cultural conceptions, the  strategies of geographic domain and the defense  of symbolic worlds, are the yarn for the principal  questions and thinking of this text. One of the  hypotheses is that the mission of Mascardi  in Patagonia is an example for understand  what principles and contradictions exist in the  civilization concept in American colonization  process.
Keywords: Missions; Jesuits; Patagonia; Imagination; Persuasion; Evangelism